Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan pada PT Arsa Indonesia Tangerang Selatan - Simanjuntak, Bella Tiara Ariesandi; Farida, Syarifah Ida (Jurnal Disrupsi Bisnis, 2024)
This study aims to determine the influence of leadership style and organizational culture on employee performance at PT ARSA Indonesia Tangerang Selatan. The method used was a quantitative method with a saturated sampling technique of 55 respondents. The data analysis method used consisted of validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, correlation coefficient, determination coefficient test, hypothesis test consisting of partial t test and simultaneous f test. The results of the study partially showed that leadership style had a positive and significant influence on employee performance with a value of t-calculus.  7,871 > ,t-table. 2.007 and significance 0.000. Organizational culture has a positive and significant influence on employee performance with a value of t-calculus. 7,403 > ,t-table. 2.007 and significance 0.000. The results of the simultaneous test of the value of F-calculate. 43,150 > ,F-table. 3.180 and a significance value of 0.000.This means that leadership style and organizational culture have an effect on employee performance with a regression of Y = 9.811 + 0.403 X1 + 0.355 X2. The contribution of influence is 62.4%.